A review of value drivers in service settings. Issue 7 (8th October 2018) - Ruiz-Molina, Maria-Eugenia; Gallarza, Martina; Gil-Saura, Irene
Abstract : Purpose: Perceived value and customer loyalty have been studied jointly in most of services literature but mainly through SEM models. This paper aims to draw on the literature on the multidimensional richness of perceived value, to adopt a segmentation approach and explore segments of loyal consumers towards the service provider based on their value perceptions. Design/methodology/approach: A survey was conducted among 460 Spanish consumers interviewed at the store exit of seven retail chains in two sectors (grocery and home furnishing). A CHAID analysis was performed on loyalty responses, through nine value dimensions (efficiency, service quality, product quality, emotional value, value for money, social value, aesthetic value, escapism and ethics). Findings: Results show the existence of different groups of loyal customers based on the nine value types. Efficiency is prioritised by the most loyal customers in grocery but not for home furnishing. Emotional value and aesthetics, along with product quality determine the most loyal segments. Practical implications: Retailers should focus on enhancing those value dimensions that better explain customer loyalty towards retail stores in their area of specialisation, combining not only tangible and intangible elements but also functional and emotional elements. Originality/value: The paper adds to the prolific research on perceived value in services with a diachronic graphical review of value dimensions in retailing; furthermore, the range of value dimensions studied here is wider than most of previous works using dimensions of value in services.